AI-Enhanced HRM: A Catalyst for Employee Innovative Work Behavior Through Autonomy, Competence, and Relatedness - Doan, Huy Hoang; Tran, Thi My Linh (Manunggal Halim Jaya, 2025)
This study explored the role of artificial intelligence (AI) in human resource management (HRM) as a motivating factor that acts as an innovation for employees, based on the Theory of Self-determination (SDT). Specifically, the study examines how AI tools support autonomy, competence, and relatedness, which can enhance the ability of employees to create, promote, and implement new ideas. A quantitative survey was done with 250 employees from organizations in Vietnam who have integrated AI into HRM practice. The results showed that AI support for autonomy (β = 0.25, p < 0.01), competence (β = 0.30, p < 0.01), and relatedness (β = 0.20, p < 0.05) significantly predict innovative behavior, explaining 45% of the variance (R² = 0.45). Support for competence emerged as a factor to predict the most powerful, stressing the importance of training personalization and real-time feedback in promoting creativity. The findings contribute to the expansion of the SDT theory in the context of HRM technology applications and provide insights and practices for organizations to leverage AI to build a culture of innovation. Research suggests that AI tools designed to meet the psychological needs of employees can transform HRM into a strategic factor supporting innovation.